ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KEBERHASILAN IMPLEMENTASI SIMRS MENGGUNAKAN OCAI dan HOT FIT - Ilen Binti Arlan (UIN Sultan Syarif Kasim Riau, 2019)
Organizational culture is very important for companies to achieve success and maintain competition between companies. One of the reasons to maintain competitive information systems needed to support the needs of the organization's services. RSUD Bangkinang has been implementing SIMRS since 2011, which found employee trends in working using SIMRS. Then it is necessary to know the organizational culture using the CVF and HOT Fit instruments as a determinant of whether SIMRS has been successfully implemented based on the existing culture. The combination of the two models produces a picture of the influence of organizational culture on the successful implementation of SIMRS. Based on the results of statistical analysis of data using SEM PLS 3.0 software, the path coefficient value of -0.077 with t value of 2.325 determines that organizational culture has a positive and significant influence on the successful implementation of SIMRS. Because culture can increase the intensity of SIMRS users, SIMRS quality and easy to learn will produce effective work, good information and can be accounted for, with the R square 93% test results that are at a strong level. Keywords: CVF, HOT Fit, Organizational Culture, SEM PLS, Successful Implementation of SIMRS